The missing hours eaudiobook A novel. - Dahl, Julia (Macmillan Audio, 2021)
From the critically acclaimed author of Invisible City and Conviction , The Missing Hours is a novel about obsession, privilege, and the explosive consequences of one violent act. From a distance, Claudia Castro has it all: a famous family, a trust fund, thousands of Instagram followers, and a spot in NYU's freshman class. But look closer, and things are messier: her parents are separating, she's just been humiliated by a sleazy documentary, and her sister is about to have a baby with a man she barely knows. Claudia starts the school year resolved to find a path toward something positive, maybe even meaningful – and then one drunken night everything changes. Reeling, her memory hazy, Claudia cuts herself off from her family, seeking solace in a new friendship. But when the rest of school comes back from spring break, Claudia is missing. Suddenly, the whole city is trying to piece together the hours of that terrible night. A Macmillan Audio production from Minotaur Books